Silicon sources can promote growth and induce systemic resistance at the microscale to control fungal diseases in sugarcane - Kauê Vinícius Cerilo; Gabrielly Caba de Oliveira; Luana Andreassa Alves; Marina Magdalena Dellapina Rodrigues; Fernanda Goncalves Martins Maia; Jader Braga Maia; Danielle Otte Carrara Castan Sarto; Marcelo Rodrigues (Acta Scientiarum. Agronomy, 2026)
Sugarcane is a crop of great economic importance for Brazil. However, it is affected by several fungal foliar diseases that compromise its agricultural productivity. The use of elicitor agents can induce and enhance plant resistance, in addition to reducing the need for pesticides, thus promoting sustainable production. Our hypothesis was that fertilization with silicon as a constituent element of the cell wall can create greater resistance and control of foliar fungal infections responsible for red rot and ringspot diseases and has a greater effect when combined with genetic resistance. The objective was to apply and investigate the potential of silicon Si as an inducer of systemic resistance and modulator of phenotype for the control of fungi in two sugarcane cultivars, RB867515, which is recognized for its greater productivity in the Iturama-Minas Gerais region, and the transgenic cultivar CTC9001BT, which has resistance to the sugarcane borer, by analyses of morphophysiological and micromorphometric parameters. The greatest discovery of this scientific research was the positive effect of greater systemic resistance of sugarcane with different management techniques: the application of Si sources resulted in the genetic transformation of plants, as observed in the CTC9001BT cultivar with higher doses of Si. Therefore, silicon may be an option for integrated pest and disease management. However, some significant differences observed in the biometric, anatomical and micromorphometric analyses may result from genetic differences between the cultivars studied.